2022
DOI: 10.1007/s00404-022-06482-8
|View full text |Cite
|
Sign up to set email alerts
|

Potential of blood-based biomarker approaches in endometrium and breast cancer: a case-control comparison study

Abstract: Purpose Endometrial carcinoma is the second most common gynecological malignancy. Until today lacking a screening tool. A blood-based biomarker could help address this need. Methods The expression levels of 30 acylcarnitines, 18 amino acids, 6 miRNAs, and 7 DNA methylation sites were measured in blood samples from 331 women (20 EC, 14 benign uterine lesions (benign), 140 breast cancers (BC), 157 controls). Areas under the ROC curves (AUC), sensitivity (sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 65 publications
(69 reference statements)
0
4
0
Order By: Relevance
“…For validation, the authors adopted a prospective design on a very large study cohort (over 1,000 subjects), therefore, candidate biomarkers identified in this study bear great potential for translation into clinical practice. Of interest, these biomarkers include steroids, which were also selected as candidate molecules in other studies (135,157) A caveat in a number of the included studies on proteomics (102, 104, 108) or metabolomics (136,138,142,143) is the use of healthy (not age/comorbidity matched) women, likely resulting in an overestimated diagnostic accuracy. Also, if pre-menopausal controls are included, this may induce biases as EC is predominantly a postmenopausal disease (114-116, 122, 147, 149, 154).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For validation, the authors adopted a prospective design on a very large study cohort (over 1,000 subjects), therefore, candidate biomarkers identified in this study bear great potential for translation into clinical practice. Of interest, these biomarkers include steroids, which were also selected as candidate molecules in other studies (135,157) A caveat in a number of the included studies on proteomics (102, 104, 108) or metabolomics (136,138,142,143) is the use of healthy (not age/comorbidity matched) women, likely resulting in an overestimated diagnostic accuracy. Also, if pre-menopausal controls are included, this may induce biases as EC is predominantly a postmenopausal disease (114-116, 122, 147, 149, 154).…”
Section: Discussionmentioning
confidence: 99%
“…A caveat in a number of the included studies on proteomics ( 102 , 104 , 108 ) or metabolomics ( 136 , 138 , 142 , 143 ) is the use of healthy (not age/comorbidity matched) women, likely resulting in an overestimated diagnostic accuracy. Also, if pre-menopausal controls are included, this may induce biases as EC is predominantly a postmenopausal disease ( 114 116 , 122 , 147 , 149 , 154 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to the review of exosomal biomarkers, 15 studies were eligible for inclusion, and these reported on 29 different exosomal biomarkers and a total of 5527 patients. Amongst this group 2530 had a diagnosis of EC and 2456 were non-cancerous control-group patients [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]. Only Mi-RNA 21, 27a, and 223 were suitable for meta-analysis as they met the inclusion criteria and were reported by two or more studies.…”
Section: Discussionmentioning
confidence: 99%